Educação sexual nos projetos políticos pedagógicos de escolas especiais - Colombo, Isabella Mota (Universidade Federal de São Carlos, 2022)
The present study deals with Sex Education offered to students with disabilities enrolled in special schools. Due to the myths and taboos surrounding the sexuality of people with disabilities, such as the belief that they are asexual or hypersexed, the Sexual Education offered to this public is done in a superficial and inadequate way. Thus, this study has the general objective of investigating whether Sexual Education is part of the Political Pedagogical Project (PPP) of special schools. And for specific purposes: (a) to analyze how Sexual Education is present in the PPP of special schools; (b) describe how Sex Education is approached with students with disabilities in a specialized school context; (c) to verify which professionals are involved in the teaching of Sexual Education to students and (d) to investigate with which students the themes involving Sexual Education are worked on. Given the above, the study has a qualitative approach with an exploratory and descriptive design, also based on document analysis. Data collection took place on the premises of four Associação de Pais e Amigos dos Excepcionais, located in small and medium-sized cities in the interior of the state of São Paulo. Three school directors and a pedagogical coordinator participated in the study, who made up the group of managers of the special schools in the study and four psychologists, who were part of the group of professionals who approach Sexual Education with students. As for the data collection procedures, the Pedagogical Political Project and/or other document concerning the pedagogical practice of the participating special schools were read and analyzed; semi-structured interviews were also carried out with the participants of the group of managers of the study individually, as well as with the participants of the study who composed the group of professionals who approach Sexual Education with students. Data were analyzed in light of content analysis. As a result, it was identified that Sex Education is present in the documents analyzed in a superficial way, that in special schools it is professionals in the field of psychology who work with Sex Education, that all participants had difficulties in conceptualizing what Sex Education is. and that the work done in this regard in the institutions studied is primarily with a view to the biological and physiological area; leaving in the background the social, political and historical approaches of Sex Education. It is concluded that there is an urgent need for initial and continuous training of professionals who work in a school environment to deal with Sexual Education, as well as for this issue to be approached in a transversal way.
Sexual education in pedagogical political projects of special schools
Keywords: Educação especial; Educação sexual; Sexualidade; Deficiência; Escolas especiais; Special education; Sex education; Sexuality; Disabilities; Special schools; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO